Characterizing reactive oxygen generation and bacterial inactivation by a zerovalent iron-fullerene nano-composite device at neutral pH under UV-A illumination - ERKEN, ESRA (ELSEVIER, 2015)
A nano-composite device composed of nano-scale zerovalent iron (ZVI) and C-60 fullerene aggregates (ZVI/nC(60)) was produced via a rapid nucleation method. The device was conceived to deliver reactive oxygen species (ROS) generated by photosensitization and/or electron transfer to targeted contaminants, including waterborne pathogens under neutral pH conditions. Certain variations of the nano-composite were fabricated differing in the amounts of (1) ZVI (0.1 mM and 2 mM) but not nC(60) (2.5 mg-C/L), and (2) nC(60) (0-25 mg-C/L) but not ZVI (0.1 mM). The generation of ROS by the ZVI/nC(60) nano-composites and ZVI nanoparticles was quantified using organic probe compounds. 0.1 mM ZVI/2.5 mg-C/L C-60 generated 3.74-fold higher O-2(center dot-) concentration and also resulted in an additional 2-log inactivation of Pseudomonas aeruginosa when compared to 0.1 mM ZVI (3-log inactivation). 2 mM ZVI/2.5 mg-C/L nC(60) showed negligible improvement over 2 mM ZVI in terms of O-2(center dot-) generation or inactivation. Further, incremental amounts of nC(60) in the range of 0-25 mg-C/L in 0.1 mM ZVI/nC(60) led to increased O-2(center dot-) concentration, independent of UV-A. This study demonstrates that ZVI/nC(60) device delivers (1) enhanced O-2(center dot-) with nC(60) as a mediator for electron transfer, and (2) O-1(2) (only under UV-A illumination) at neutral pH conditions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Nano-scale zerovalent iron; Fullerene; Nano-composite; Reactive oxygen species; Photosensitization; ZERO-VALENT IRON; OXIDATIVE-DEGRADATION; ORGANIC-COMPOUNDS; ELECTRON-TRANSFER; SINGLET OXYGEN; NANOPARTICLES; POLYOXOMETALATE; DECHLORINATION; PARTICLES; REMOVAL